Study of the operation of a compact regenerator with different nozzles - Romanko , Ya.V.; Mieshkova , A.H.; Gupalo , O.V. (Theory and Practice of Metallurgy, 2025)
The object of the study is the heat exchange processes in the working space of the nozzle of a high-temperature compact regenerative heat exchanger in the smoke and air periods. The purpose of the study is to determine the influence of the characteristics of various heat-accumulating nozzles of the regenerator on the thermal efficiency of its operation and to determine the operating characteristics of the regenerator when combining nozzles of different types. Using a mathematical model, the operation of a compact regenerative heat exchanger with different types of nozzles was investigated under the conditions of its use together with a burner in the heating system of a high-temperature heat-technical unit. Calculations of the operation of the regenerator with a ball nozzle, with a honeycomb nozzle and with a nozzle consisting of a layer of balls and porous ceramic blocks were performed.